(untitled) (Annals of Medical Research, 2021)
Aim: Spinal cord traumas have become a serious health problem with the increase in the ageing population in society. The present study aimed to show the anti-inflammatory activity of methylprednisolone and sinularia administered following spinal cord trauma.Materials and Methods: Sea corals are widely found on earth. Sinularia is one of the 17 known active substances of sinularia flexibilis, and several studies have been conducted on its anti-inflammatory, anti-oedema and cytotoxic effects. Despite the recent scientific studies, discussions continue as there are no effective treatment methods in use apart from methylprednisolone; however, the test animals received methylprednisolone treatment to compareits effects with those of sinularia, a secondary active ingredient of s. flexibilis.Results: Paired comparisons for serum IL-1β and tissue TNF-α were made with Dunn’s test. When serum IL-1β and tissue TNF-α levels were evaluated, a significant difference was detected in the group taking sinularia treatment compared to the trauma group Sinularia treatment was more efficient on different cytokines and compared to methylprednisolone treatment used routinely, it significantly affected both IL-1β level and TNF-α levels in serumConclusion: Anti-edematous, cytotoxic and anti-inflammatory effects of sinularia have been shown in our study. Sinularia, which has no known harmful effect on the human body according to the literature, may be clinically used in the future; however, more detailed and supportive experimental studies should be conducted on the subject.